The Use of Digital Story Telling to Teach Listening: A Classroom Action Research to XA Grade Students of SMA Santo Fransiskus Asisi Pontianak - Derek, Vandrektus; Regina, Regina; Ikhsanudin, Ikhsanudin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to describe how the use of digital storytelling impact the tenth-grade (X.A) students at SMA Santo Fransiskus Asisi Pontianak in learning listening comprehension. The animation stories of digital form were served to bring the engagement among students in listening activities. The listening activity was done with the assistance of audio visual media by manipulating the original story to the new version. Then, the story board was rearranged to associate the students’ listening comprehension to the changing plot of the story being played. The research used classroom action research conducted in two cycles. Every cycle consisted of four steps such as planning, action, evaluation, and reflection. The data in every learning cycle were presented quantitatively based on the indicator and described in qualitative descriptions. The weakness in one cycle was revised, and did the following cycle with the same steps but with the revised lesson plan. Research instruments were constructed in the form of assessment rubric, field note, and observation instrument to the lesson plan and teaching process. The findings revealed that the students showed their positive changes from one cycle to the next cycle in terms of engagement and listening comprehension. As a result, the use of digital storytelling to teach listening improves the students’ engagement and impacts positively to the achievement on listening comprehension through the medium of animation of fractured story.